Towards Building A Group-based Unsupervised Representation Disentanglement Framework - Yang, Tao; Ren, Xuanchi; Wang, Yuwang; Zeng, Wenjun; Zheng, Nanning (ICLR 2022, 2022)
Disentangled representation learning is one of the major goals of deep learning, and is a key step for achieving explainable and generalizable models. The key idea of the state-of-the-art VAE-based unsupervised representation disentanglement methods is to minimize the total correlation of the joint distribution of the latent variables. However, it has been proved that their goal can not be achieved without introducing other inductive biases. The Group Theory based definition of representation disentanglement mathematically connects the data transformations to the representations using the formalism of group. In this paper, built on the group-based definition and inspired by the [n-th dihedral group], we first propose a theoretical framework towards achieving unsupervised representation disentanglement. We then propose a model based on existing VAE-based methods to tackle the unsupervised learning problem of the framework. In the theoretical framework, we prove three sufficient conditions on model, group structure, and data respectively in an effort to achieve, in an unsupervised way, disentangled representation per group-based definition. With these conditions, we offer an option, from the perspective of the group-based definition, for the inductive bias that existing VAE-based models lack. Experimentally, we train 1800 models covering the most prominent VAE-based methods on five datasets to verify the effectiveness of our theoretical framework. Compared to the original VAE-based methods, these Groupified VAEs consistently achieve better mean performance with smaller variances.